تطور مهنة العازفة خلال العصرين الكلاسيكي والهيلينستي - عامر، هبة حسن أحمد (جامعة عين شمس - مركز الدراسات البردية والنقوش, 2022)
لعبت الموسيقى دورا مهما في العديد من جوانب الحياة في بلاد اليونان القديمة، سواء في المناسبات الاجتماعية اليومية، أو في الطقوس الدينية المختلفة، وغيرها من المناسبات الدينية والمدنية. وتغيرت أنواع الموسيقى وإيقاعاتها وفقا للحدث الذي شاركت به، سواء كان عملا مسرحيا أم حدثا دينيا أو اجتماعيا، وغالبا ما ساهمت جميع العوامل السابقة في تحديد المكانة الاجتماعية للعازفين الموسيقيين. يتناول هذا البحث تطور مهنة العازفة خلال العصرين الكلاسيكي والهلينستي؛ وأهمية دور العازفات في الحفلات والمناسبات الاجتماعية والدينية المختلفة. والعوامل التي أثرت في المكانة الاجتماعية للنساء اللواتي مارسن تلك المهنة. والعوامل التي أدت إلى تطور مستوى مهارتهن وعلو مكانتهن. ونظرة المجتمع لمهنة العازفة من خلال المصادر الأدبية والنقوش. Music had a significant role in many aspects of life in ancient Greece, whether in daily social events or in various religious rituals and other religious and civil events. The types of music and their rhythms changed according to the event taking place, whether theatrical work, religious or social event, and often all the previous factors contributed to determining their social status of musicians. This paper deals with the development of the profession of the female music player during the classical and the Hellenistic eras. Moreover, it reveals the importance of their role at the concerts and various social and religious occasions. as well as the factors that affected the social status of them. In addition, the study shows the factors that led to the development of their skill level and the honors they received. Finally, it points the society's view of their profession through literary sources and inscriptions.
Keywords: الفن الموسيقي -- المناسبات الاجتماعية -- الطقوس الدينية -- العازفين الموسيقيين -- التراث الفني